To establish the reference range of glycated hemoglobin - Dogra, Nisha; Bhaskar, Neeru; Pandey, Rajesh; Prasad, Suvarna; Singh, Jasbir; Sodhi, Kuldip Singh (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus (DM) has emerged as a major healthcare problem in India. There were an estimated 40 million persons with DM in India in 2007 and this number is predicted to rise to almost 70 million by 2025. It is estimated that every fifth person with diabetes will be an Indian. The objective of the present investigation was to establish the reference range for glycated hemoglobin (HbA1C) in healthy non-diabetic subjects in our hospital laboratory and compare it with the values reported by standard laboratories. Methods: The study was conducted in the Department of Biochemistry, MMIMSR, Mullana (Ambala, Haryana). Total number of subjects was 50 (25 males, 25 females), aged 30 to 70 years. 2 ml of blood was collected from antecubital vein under aseptic conditions from each subject and put in EDTA vials. Hemolysed blood was estimated by semiautoanalyzer for HbA1C. Results: In females, the levels were 6.50 ± 0.74 % while in males the levels were 6.27 ± 0.94 %. The overall range in females was 4.8 - 7.56 % while in males it was 4.2 to 7.56 %. The values were comparable (p>0.05) with those reported by standard laboratories, e.g. Dr. Lal PathLabs (<6%), Charak diagnostic (4.5-6.3%) and Mayo Clinic (6.5-7%). Conclusion: Our laboratory levels of HbA1C are comparable with the reference range of different laboratories and hence suitable to be used as cut-offs while interpreting the results of patients with DM.